Discrete Sliding Mode control of LCL Grid Connected Inverter Under Distorted Grid Voltage - Makhamreh, Hamza; Kukrer, Osman (IEEE, 2018)
In this paper, a discrete based sliding mode controller is applied to LCL grid connected inverter. The control input is derived based on feed-forward control of the model in addition to discrete sliding mode control (DSMC). Feed-forward control part contributes with most of the control input, while DSMC improves the system's steady state error and increase fast transient response. Additionally, a nonlinear part is added based on reaching law approach to improve the robustness and disturbance rejection. Simulations are performed under totally distorted grid voltage, and the controller was able to inject pure sinusoidal grid reference current at fast response.
12th IEEE International Conference on Compatibility, Power Electronics and Power Engineering (CPE-POWERENG) -- APR 10-12, 2018 -- Doha, QATAR
Keywords: Sliding mode control; discrete-time systems; distorted grid voltage; LCL grid connected inverter